Remote sensing as a tool to survey endemic diseases in Brazil - Virginia Ragoni de Moraes Correia; Marilia Sá Carvalho; Paulo Chagastelles Sabroza; Cíntia Honório Vasconcelos
The objective of this study, based on a systematic literature review, is to present the characteristics and potentialities of remote sensing as a useful environmental surveillance tool for applied research in the control of endemics in Brazil. Onboard satellite sensors allow for monitoring the territory, furnishing spatial and temporal information on various scales and regions in the electromagnetic spectrum. Based on the literature review on the application of this technology to the study of endemics and the identification of the potential of new sensors with better spectral, spatial, and temporal resolutions, this study highlights perspectives for the use of remote sensing in the study of important endemics for Brazil.